2016
DOI: 10.1097/moh.0000000000000213
|View full text |Cite
|
Sign up to set email alerts
|

Should acute myeloid leukemia patients with actionable targets be offered investigational treatment after failing one cycle of standard induction therapy?

Abstract: The relative value of different treatment strategies if a first standard induction therapy cycle fails to produce complete remission is unknown. However, retreatment with the same therapy often leads to complete remission and provides a benchmark against which other approaches should be compared. Addition of investigational small molecule drugs to standard reinduction therapy in patients with actionable targets could offer an attractive therapeutic strategy in this situation that might improve outcomes and fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The 5-year RFS was 16% for MRD-positive patients and 43% for patients with no evidence of residual disease (p<0.001) 60. Thus, a rapid decline in MRD levels after induction therapy may reflect a highly chemo-sensitive disease with a “per se” favorable prognosis 61. Early MRD clearance was also prognostic within the intermediate cytogenetic risk group (5-year RFS 15% vs 37%, P= 0.016) as well as for patients with normal karyotype and NPM1 mutations (5-year RFS 13% vs 49%, P=0.02) or FLT3-ITD (3-year RFS rates 9% vs 44%, P=0.016) 60.…”
Section: Mrd Detection By Mpfcmentioning
confidence: 99%
“…The 5-year RFS was 16% for MRD-positive patients and 43% for patients with no evidence of residual disease (p<0.001) 60. Thus, a rapid decline in MRD levels after induction therapy may reflect a highly chemo-sensitive disease with a “per se” favorable prognosis 61. Early MRD clearance was also prognostic within the intermediate cytogenetic risk group (5-year RFS 15% vs 37%, P= 0.016) as well as for patients with normal karyotype and NPM1 mutations (5-year RFS 13% vs 49%, P=0.02) or FLT3-ITD (3-year RFS rates 9% vs 44%, P=0.016) 60.…”
Section: Mrd Detection By Mpfcmentioning
confidence: 99%
“…Several studies have demonstrated that patients entering an MRD neg CR early, i.e. with one cycle of standard induction chemotherapy, have a substantially lower relapse risk and live longer than other similarly-treated patients [43]. Possible strategies to augment subsequent therapy for MRD pos patients could include the intensification of post-remission therapy cycles (e.g.…”
Section: Where Should We Go With Mrd-directed Therapy Of Non-apl Aml?mentioning
confidence: 99%